Microcapsules engineered to support mesenchymal stem cell (MSC) survival and proliferation enable long-term retention of MSCs in infarcted myocardium. (June 2015) - Blocki, Anna; Beyer, Sebastian; Dewavrin, Jean-Yves; Goralczyk, Anna; Wang, Yingting; Peh, Priscilla; Ng, Michael; Moonshi, Shehzahdi S.; Vuddagiri, Susmitha; Raghunath, Michael; Martinez, Eliana C.; Bhakoo, Kishore K.
Abstract: The limited efficacy of cardiac cell-based therapy is thought to be due to poor cell retention within the myocardium. Hence, there is an urgent need for biomaterials that aid in long-term cell retention. This study describes the development of injectable microcapsules for the delivery of mesenchymal stem cells (MSCs) into the infarcted cardiac wall. These microcapsules comprise of low concentrations of agarose supplemented with extracellular matrix (ECM) proteins collagen and fibrin. Dextran sulfate, a negatively charged polycarbohydrate, was added to mimic glycosaminoglycans in the ECM. Cell viability assays showed that a combination of all components is necessary to support long-term survival and proliferation of MSCs within microcapsules. Following intramyocardial transplantation, microcapsules degraded slowly in vivo and did not induce a fibrotic foreign body response. Pre-labeling of encapsulated MSCs with iron oxide nanoparticles allowed continued cell-tracking by MRI over several weeks following transplantation into infarcted myocardium. In contrast, MSCs injected as cell suspension were only detectable for two days post transplantation by MRI. Histological analysis confirmed integration of transplanted cells at the infarct site. Therefore, microcapsules proved to be suitable for stem cell delivery into the infarcted myocardium and can overcome current limitations of poor cell retention in cardiac cell-based therapy.